2006
DOI: 10.1016/j.str.2006.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Specific Binding of Huntingtin Proline-Rich Region with the SH3 and WW Domains

Abstract: The interactions of huntingtin (Htt) with the SH3 domain- or WW domain-containing proteins have been implicated in the pathogenesis of Huntington's disease (HD). We report the specific interactions of Htt proline-rich region (PRR) with the SH3GL3-SH3 domain and HYPA-WW1-2 domain pair by NMR. The results show that Htt PRR binds with the SH3 domain through nearly its entire chain, and that the binding region on the domain includes the canonical PxxP-binding site and the specificity pocket. The C terminus of PRR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 57 publications
(67 reference statements)
0
35
0
Order By: Relevance
“…1A) (24). Our previous work identified that the first and third portions of Htt PRR specifically interact with the tandem WW domains (13). To better understand how the tandem WW domains of HYPA interact with the Htt PRR motif, we used GST pulldown experiments to characterize the interactions between N-terminal Htt and different GST-fused WW domains (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1A) (24). Our previous work identified that the first and third portions of Htt PRR specifically interact with the tandem WW domains (13). To better understand how the tandem WW domains of HYPA interact with the Htt PRR motif, we used GST pulldown experiments to characterize the interactions between N-terminal Htt and different GST-fused WW domains (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The proteins were purified by Ni 2ϩ -NTA affinity column followed by gel filtration chromatography. 15 N/ 13 C-Labeled proteins were prepared by using the M9 minimal medium containing 15 15 N/ 13 C-labeled 2WW-P67T protein in a phosphate buffer (10 mM, pH 6.0) was used for the structural determination by NMR as our previous study (13). All data acquisition was carried out at 25°C on a Varian INOVA 600 spectrometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atx7 PP2 and SH3C bind by isothermal titration calorimetry (View Interaction: 1,2,3,4,5,6,7,8,9,10,11,12) Atx7 binds to SH3C by pull down (View interaction) Atx7 100Q and SH3C colocalize by fluorescence microscopy (View interaction) SH3C and Atx7 bind by nuclear magnetic resonance (View interaction)…”
Section: Structured Summary Of Protein Interactionsmentioning
confidence: 99%
“…After purification, MTSL ((1-oxyl-2,2,5,5-tetramethyl pyrroline-3-methyl) methanethiosulfonate) (ALEXIS Biochemicals, San Diego) was incubated with Atx7_PP2 at 4°C overnight. Ten-fold excess of MTSL was used for the reaction and the excess MTSL was removed by desalting [11]. In the PRE experiment, after collecting a HSQC spectrum, dithiothreitol (DTT, 10 mM) was added to the mixture in the NMR tube and stayed at room temperature for 5 h to remove MTSL from the Atx7_PP2 peptide, and then another HSQC spectrum was acquired for reference [15].…”
Section: Mtsl Labeling and Paramagnetic Relaxation Enhancement (Pre)mentioning
confidence: 99%